Tren, Efektivitas, dan Kontribusi Etnomatematika dalam Pembelajaran Matematika SD terhadap Pelestarian Budaya: Kajian Literatur Sistematis - Malihatin Malihatin; Eko Handoyo; Hanafi Hussin; Indriana Eko Armadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to map the trends, integration forms, effectiveness, and contribution of ethnomathematics in elementary school mathematics learning toward national cultural preservation. A systematic literature review (SLR) approach following the PRISMA 2020 protocol was employed. Searches across four academic databases (Scopus, Google Scholar, CrossRef, and Semantic Scholar) yielded 1,176 articles, from which 30 articles met the inclusion criteria. Results indicate that ethnomathematics research in elementary schools has increased significantly during 2023–2026, particularly following the implementation of Kurikulum Merdeka. The three most dominant forms of integration are digital modules and media (53.3%), traditional games (33.3%), and ethnomathematics-based worksheets (13.3%). Geometry and measurement is the most researched mathematics topic (50.0%), and conceptual understanding shows the most significant improvement (40.0%). Beyond improving mathematics achievement, ethnomathematics integration contributes to cultural preservation through cultural contextualization in learning (60.0%), strengthening cultural identity and values (26.7%), and active local cultural preservation (10.0%). The study recommends teacher training, curriculum policy strengthening, cross-sector collaboration, and further research to sustain ethnomathematics implementation in Indonesian elementary schools.